Virus Injection to the Pituitary via Transsphenoidal Approach and the Innervation of Anterior and Posterior Pituitary of Rat - Li, Xiaohui; Su, Shanchun; Zhao, Haiwen; Li, Yang; Xu, Xueqin; Gao, Yan; Sun, Dongsheng; Yang, Zeyong; Jin, Weilin; Ke, Changbin (Frontiers in Endocrinology, 2020)
The theory holds that the anterior pituitary in mammals receives humoral regulation. Previous studies have reported that the pars distalis of the anterior pituitary of several mammalian species contains substance P-, calcitonin gene-related peptide (CGRP)-, and galanin-like immunoreactive nerve fibers, but the origins of these nerve fibers are unclear. Removal of the pituitary gland, also called hypophysectomy, involves methods that access the pituitary gland via the transauricular or parapharyngeal pathways. However, these methods are not applicable for viral tracer injection to investigate the innervation of the anterior pituitary. The transauricular technique leads to inaccuracies in locating the pituitary gland, while the parapharyngeal approach causes high mortality in animals. Here, we introduce a protocol that accesses the pituitary gland in the rat via the transsphenoidal pathway. This method imitates surgical manipulations such as endotracheal intubation and sphenoid bone drilling, which involve the use of custom-made devices. Using the transsphenoidal pathway greatly improves the survival rate of rats because no additional dissection of blood vessels and nerves is required. Moreover, the pituitary gland can be viewed clearly and directly during the operation, making it possible to accurately inject pseudorabies virus (PRV) 152-expressing enhanced green fluorescent protein (EGFP) into the anterior or posterior pituitary, respectively. After injecting PRV 152 into the anterior pituitary, we found no evidence of direct innervation of the anterior pituitary in the rat brain. However, PRV 152 injection into the posterior pituitary revealed retrograde transneuronal cell bodies in many brain areas, including the CA1 field of the hippocampus, the basolateral amygdaloid nucleus, posterior part (BLP), the arcuate hypothalamic nucleus (Arc), the dorsal portion of the dorsomedial hypothalamic nucleus (DMD), the suprachiasmatic nucleus (SCh), and the subfornical organ (SFO). In the present study, we provide a description of a possible model of hypophysectomy or pituitary injection, and identify brain regions involved in regulating the rat pituitary gland using transneuronal retrograde cell body labeling with PRV.